Combination of Sulfur Dioxide-Generating Pads Reduces Gray Mold Disease Caused by Botrytis cinerea in ‘BRS Vitoria’ Hybrid Seedless Grapes during Cold Storage - Aline Cristina de Aguiar; Bruna Evelise Bosso Caetano; Sergio Ruffo Roberto (Horticulturae)
This study aimed to assess the cold storage preservation of ‘BRS Vitoria’ seedless grape by combining SO2-generating pads. ‘BRS Vitoria’ grapes were freshly harvested from a commercial vineyard in Marialva, PR, Brazil. The trial was carried out in a completely randomized design with four treatments and five replications, and each plot consisted of five bunches individually packaged in clamshells. Treatments included (a) control (without SO2 pads), (b) field ultrafast SO2-generating pad before packaging (FieldSO2), (c) dual-release SO2-generating pad during cold storage (DualSO2), and (d) FieldSO2 + DualSO2. After being harvested, bunches subjected to FieldSO2 treatments were placed in a 20 kg harvest box with perforated liners. Subsequently, the FieldSO2 was placed on top of the grapes, and the liner was sealed for 4 h. Afterwards, bunches were packaged according to the treatments, and the boxes were kept in cold storage (1 °C ± 1 °C) for 60 days and at room temperature for 3 days. After 60 days of cold storage, by using a combination of FieldSO2 and DualSO2 pads, the cold preservation of ‘BRS Vitoria’ grape bunches can be extended up to 60 days with total absence of gray mold with fresh stems, with no negative impact on weight loss, shattered berries or even bleaching. This treatment can be used to optimize the cold storage period of ‘BRS Vitoria’, especially for export markets, where long periods of cold preservation are required.